Prognostic Value of Various Hemostasis Parameters and Neurophysiological Examinations in Spontaneous Intracerebral Hemorrhage: The IRONHEART Study Protocol - Árokszállási, Tamás; Héja, Máté; Bagoly, Zsuzsa; Kovács, Kitti Bernadett; Orbán-Kálmándi, Rita; Sarkady, Ferenc; Tóth, Judit; Fekete, Klára; Fekete, István; Csiba, László (Frontiers in Neurology, 2021)
Rationale: Stroke is one of the leading causes of death in all developed countries. In Hungary, more than 10,000 patients die annually due to cerebrovascular diseases according to the WHO Mortality Database. Of these patients, 10–15 % suffer non-traumatic intracerebral hemorrhage (ICH). ICH results in a higher rate of mortality as compared to ischemic stroke and outcomes are difficult to predict. In the IRONHEART study, we aim to test various hemostasis parameters and clinical neurophysiological examinations in evaluating outcome in ICH. Methods: In this prospective, observational study, we plan to enroll consecutive patients with non-traumatic spontaneous ICH admitted to a single Stroke Center (Department of Neurology, University of Debrecen, Hungary). The protocol of the IRONHEART study includes the investigation of detailed clinical, laboratory investigations, and various neurophysiological examinations. Stroke severity is quantified based on the National Institutes of Health Stroke Scale (NIHSS) on admission and day 7, 14, and 90 after the onset of stroke. Cranial CT is performed on admission, day 14, and 90 to estimate the ICH volume. Modified Rankin Scale (mRS) is used for evaluating the long-term outcome (90 days post-event). Blood is drawn immediately on admission for specific hemostasis tests. Digital and quantitative EEG techniques and motor evoked potential (MEP) are performed to evaluate the prognosis of cerebral hemorrhage on admission (within 24–48 h), immediately before discharge ( 10–14 days later), and 3 months after the event. Outcomes: The following outcomes are investigated: primary outcomes: mortality by day 14 and day 90, secondary long-term outcome at 90 days post-event where mRS 0–2 is defined as favorable long-term outcome. Discussion: If associations between outcomes and the investigated parameters (hemostasis and neurophysiological examinations) are confirmed, results might aid prognosis assessment in this subtype of stroke with particularly high mortality. Improving clinical grading systems on ICH severity and outcomes by including the investigated parameters could help to better guide the management of these patients in the future.